The Synthesis of Size-Adjustable Superparamagnetism Fe3O4 Hollow Microspheres - Chao Xu; Xiaolong Lu; Honglian Dai (Nanoscale Research Letters, 2017)
Abstract One hundred fifty to 300-nm-sized monodisperse iron oxide (Fe3O4) hollow microspheres were synthesized by the one-pot hydrothermal method. The morphology and crystal structure of the as-prepared hollow microspheres was characterized by scanning electron microscopy, X-ray diffraction, transmission electron microscopy, and high-resolution transmission electron microscopy, while the magnetic property was investigated by vibrating sample magnetometer. We found that the particle size of the hollow microspheres was related to the amount of sodium citrate, polyacrylamide (PAM), and urea. The hollow structure of Fe3O4 microspheres has high magnetization saturation values ranging in 49.10–75.41 emu/g.